1991
DOI: 10.1007/bf00191095
|View full text |Cite
|
Sign up to set email alerts
|

Case report 690

Abstract: Nodular fasciitis is an uncommon, benign, reactive process of the soft tissues related to the fascia. It occurs most commonly in the extremities, trunk, face, and neck. The lesion may grow rapidly and mimic a malignant process. It received little attention in the radiological literature. We describe the MRI features of nodular fasciitis in a patient with a lesion in the right elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Only one case of nodular fasciitis of the elbow has been described previously, but no tumor was present within the elbow joint [10]. Hornick et al reported 10 cases of intra-articular nodular fasciitis, with seven lesions arising in the knee, two in the hand, and one in the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of nodular fasciitis of the elbow has been described previously, but no tumor was present within the elbow joint [10]. Hornick et al reported 10 cases of intra-articular nodular fasciitis, with seven lesions arising in the knee, two in the hand, and one in the ankle.…”
Section: Discussionmentioning
confidence: 99%